Traditional Dance Learning to Enhance Self-Confidence in Early Childhood - Indriani, Avianti; Anggraini, Henni; Kumala, Farida Nur (Transpublika Publisher, 2025)
The background of this study departs from the importance of the development of socio-emotional aspects of early childhood, especially self-confidence, which is an important foundation in the formation of character and adaptability of children. This study aims to determine the learning of dance can increase the confidence of children aged 5-6 years in KB PKK AL Mubarok Karanganyar. The research method used is Class Action Research (PTK) with a qualitative mixed approach. The subjects of the study were 11 children of Group B2 aged 5-6 years. Data collection techniques included observation, interviews, and documentation, with indicators of self-confidence including the courage to try new things, the ability to interact, not giving up easily, and the courage to express themselves. The results showed that learning to dance can significantly increase children's self-confidence. This can be seen from the increase in observation scores in cycle I by 58.5% showed a level of confidence and up 9% from pre-cycle conditions and an increase in confidence of 22.5% from cycle I conditions in Cycle II. Learning the art of Dance provides space for children to express, improve motor coordination, and form a positive self-image. This study concludes that dance is effective as a learning medium in increasing early childhood self-confidence and has important implications for culture-based educational practices.